Taxonomy of the genus Miobdelus Sharp, 1889 (Coleoptera: Staphylinidae: Staphylinini) and five new species from China - He, Liang; Zhou, Hong-Zhang (Zootaxa, 2018)
Five new species of the rove beetle genus Miobdelus Sharp, 1889 are described from South China: Miobdelus wolongensis He and Zhou, sp. nov., Miobdelus wangi He and Zhou, sp. nov., Miobdelus chrysanthemoides He and Zhou, sp. nov., Miobdelus chrysochromatus He and Zhou, sp. nov. and Miobdelus baoxingensis He and Zhou, sp. nov. Line drawings and color illustrations of adults and genitalia are given for the five new species, as well as other twelve known species, namely, Miobdelus atricornis Smetana, 2001, Miobdelus biseriatus Smetana, 2001, Miobdelus caelestis Smetana, 2001, Miobdelus egregius Smetana, 2001, Miobdelus eppelsheimi (Reitter, 1887), Miobdelus gemellus Smetana, 2005, Miobdelus inornatus Smetana, 2001, Miobdelus insignitus Smetana, 2011, Miobdelus insolens Smetana, 2011, Miobdelus kubani Smetana, 2001, Miobdelus lacustris Smetana, 2001 and Miobdelus purpurascens Smetana, 2001. A key to all the species of the genus Miobdelus Sharp, 1889 is provided.